School Management System Assistance with Technology Awareness at SMP Negeri 13 Dumai - Sri Yuliani; Yulianto; Sri Rahayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The assistance of the school management system is carried out at one of the driving schools in Dumai, namely SMP Negeri 13 Dumai. The implementation of this school management system assistance program aims to provide assistance to teachers at SMP Negeri 13 Dumai for the use of technology awareness available at the school. The methods used in this activity are lectures, workshops, and mentoring methods. Evaluation is done by observing the skills of staff, teachers, librarians, and laboratory assistants in mastering the technology that has been implemented. The result achieved in this service is an increase in technology awareness capabilities at the management level of which can be measured from three main factors, namely: (1) increasing their knowledge about awareness in the field of sensitivity (perceptual component) where managerial staff in SMP Negeri 13 Dumai is able to identify and implement existing technology in the field of education (2) second component, insight (interpretation component) where insight, the ability of managerial staff in this school to understand the reasons for mastering renewable technology for efficiency and effectiveness in the school management system and (3) the third component is communication. Through this community service activity, it is hoped that the staff and management will increase the awareness of using appropriate technology in the smooth running of educational and the next hope is that partner schools at SMP Negeri 13 Dumai and partner teachers will provide a positive response to the implementation of the mentoring system of school management.